Substituting TiCl4-Carbon Nanohorn Interfaces for Dye-Sensitized Solar Cells - Casillas Pacheco, Ruben; Lodermeyer, Fabian; Costa, Ruben Dario; Prato, Maurizio; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
An easy-to-implement strategy to introduce carbon nanohorns as interlayers in the photoelectrode of a dye-sensitized solar cell without affecting its overall performance is presented. This provides a clean, easy, and ecofriendly alternative to achieve highly efficient cells.